Correlated Insulating Behavior in Infinite-Layer Nickelates - Hsu, Y.-T.; Osada, M.; Wang, B. Y.; Berben, M.; Duffy, C.; Harvey, S. P.; Lee, K.; Li, D.; Wiedmann, S.; Hwang, H. Y.; Hussey, N. E. (Frontiers in Physics, 2022)
Unlike their cuprate counterparts, the undoped nickelates are weak insulators without long-range antiferromagnetic order. Identifying the origin of this insulating behavior, found on both sides of the superconducting dome, is potentially a crucial step in the development of a coherent understanding of nickelate superconductivity. In this work, we study the normal-state resistivity of infinite-layer nickelates using high magnetic fields to suppress the superconductivity and examine the impact of disorder and doping on its overall temperature (T) dependence. In superconducting samples, the resistivity of Nd- and La-based nickelates continues to exhibit weakly insulating behavior with a magnitude and functional form similar to that found in underdoped electron-doped cuprates. We find a systematic evolution of the insulating behavior as a function of nominal hole doping across different rare-earth families, suggesting a pivotal role for strong electron interactions, and uncover a correlation between the suppression of the resistivity upturn and the robustness of the superconductivity. By contrast, we find very little correlation between the level of disorder and the magnitude and onset temperature of the resistivity upturn. Combining these experimental observations with previous Hall effect measurements on these two nickelate families, we consider various possible origins for this correlated insulator behavior and its evolution across their respective phase diagrams.